PENDIDIKAN AKHLAK DI PONDOK PESANTREN SALAFIYAH AL-ILYAASIYAH CILENGKRANG CIBIRU BANDUNG - Muhammad Hasan Basari; Fitri Handayani; Nurwadjah Ahmad; Andewi Suhartini (Pascasarjana Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
Salafiyah Islamic boarding schools with traditional characteristics, either from clothing or learning. The study of classical Islamic books or the yellow book is one of the characteristics of the Salaf Islamic boarding school. The purpose of this article is to describe the moral education in the Al-Ilyaasiyah Islamic boarding school, Cilengkrang, Cibiru Bandung. The method used in this study used a qualitative approach with descriptive analytic studies. The research instruments used were data collection techniques with observation, interviews, and library research as well as documents that support this research. The results showed that. Moral education and religious habituation at the Salafiyah Al-Ilyaasiyah Islamic boarding school, Cilengkrang, Cibiru Bandung, are carried out with strong habituation and imitation and are still carried out and immovable in the midst of technological progress and the times